2013
DOI: 10.1038/ncomms3051
|View full text |Cite
|
Sign up to set email alerts
|

Electric in-plane polarization in multiferroic CoFe2O4/BaTiO3 nanocomposite tuned by magnetic fields

Abstract: Ferrimagnetic CoFe 2 O 4 nanopillars embedded in a ferroelectric BaTiO 3 matrix are an example for a two-phase magnetoelectrically coupled system. They operate at room temperature and are free of any resource-critical rare-earth element, which makes them interesting for potential applications. Prior studies succeeded in showing strain-mediated coupling between the two subsystems. In particular, the electric properties can be tuned by magnetic fields and the magnetic properties by electric fields. Here we take … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
91
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(105 citation statements)
references
References 28 publications
9
91
0
1
Order By: Relevance
“…X-ray absorption spectroscopy and its associated x-ray linear dichroism (XLD) at the Ti L3,2 absorption edges have been shown to be a valuable tool to investigate the magnetic field-dependent electric polarisation [20]. Measurement of TEY is a possibility to detect the coupling in a surface sensitive mode since the information depth is limited by the electron escape depth, i.e.…”
Section: Magnetoelectric Couplingmentioning
confidence: 99%
See 1 more Smart Citation
“…X-ray absorption spectroscopy and its associated x-ray linear dichroism (XLD) at the Ti L3,2 absorption edges have been shown to be a valuable tool to investigate the magnetic field-dependent electric polarisation [20]. Measurement of TEY is a possibility to detect the coupling in a surface sensitive mode since the information depth is limited by the electron escape depth, i.e.…”
Section: Magnetoelectric Couplingmentioning
confidence: 99%
“…The electric field vector for horizontally polarized x-rays was parallel to the magnetic field vector, whereas the electric field vector for vertically polarized x-rays lay in the sample plane. A detailed description and illustration of the measurement geometry can be found elsewhere [20].…”
Section: Experimental Techniquesmentioning
confidence: 99%
“…• Charge order of high-Tc Superconductors (Blanco-Canosa et al, 2013;Comin et al, 2014;da Silva Neto et al, 2014;Fink et al, 2009;Ghiringhelli et al, 2012) • Coupling of electronic / lattice degrees of freedom in multiferroic materials (Glavic et al, 2013;Partzsch et al, 2011;Schierle et al, 2010;Schmitz-Antoniak et al, 2013;Skaugen et al, 2015) • Microcrystals of novel materials (Leininger et al, 2011;Matsuda et al, 2015) • Interfacial electronic properties in heterostructures (Frano et al, 2013;Wadati et al, 2009) • Element-speci c magnetic hysteresis loops (Radu et al, 2012) • Single molecular magnets (Bernien et al, 2015;Hermanns et al, 2013) • Electronic depth pro les • Electronic ground states and phase transitions in correlated materials (Schmitz et al, 2014;Strigari et al, 2013;Willers et al, 2012Willers et al, , 2011 • Magnetic clusters in carbon nanotubes (Shiozawa et al, 2015) • Nanoparticles for medical applications (Graf et al, 2015) • Magnetic semiconductors (Khalid et al, 2014) …”
Section: Applicationsmentioning
confidence: 99%
“…This type of nanostructure containing nanopillars of ferro/ferrimagnet has then been further investigated by other researchers. Schmitz-Antoniak et al [12] have analyzed the strain-mediated coupling between the two subsystems, CFO and BTO. They demonstrated that an in-plane magnetic field broke the tetragonal symmetry of the (1,3)-type CFO/BTO structures.…”
Section: Introductionmentioning
confidence: 99%